Friar Casimiro Brochtrup OFM: An Experience of the Catholic Church in the Brazilian Urban Context (1891-1945) - Marroquim, Dirceu (Studies in church history, 2025)
This article examines the role of the Catholic Church in the Brazilian city of Recife, in the aftermath of the Republic's Proclamation and the subsequent separation of church and state in Brazil. The study focuses on Friar Casimiro Brochtrup, OFM, who arrived in Brazil in 1894 and settled in Recife. His efforts in the impoverished Santo Amaro neighbourhood, particularly at Sítio da Macacheira, involved founding a church, chapels, schools and associations. The study aims to understand the Catholic Church's impact on urban territorialities amid ecclesiastical transformations and political shifts before the emergence of the theology of liberation in the late 1960s and early 1970s. It argues that the church's expansion from the late nineteenth to the early twentieth century involved territorial boundary expansion and rationalization of social assets. Drawing on diverse sources, including newspapers, ecclesiastical documents, reports and personal correspondence, this article illuminates the dynamic interactions between the Catholic Church, urban development and societal changes in Brazil during this period.